Detailed structural analyses and viscoelastic properties of nano-fibrillated bacterial celluloses - Haruto Tsujisaki; Masaaki Hosokawa; Yuichi Takasaki; Yoshifumi Yamagata; Yui Kawabata; Daisuke Tatsumi; Shuichiro Seno; Keisuke Miyamoto; Takuya Isono; Takuya Yamamoto; Hirofumi Tani; Toshifumi Satoh; et al. (Carbohydrate Polymer Technologies and Applications)
Nano-fibrillated bacterial cellulose (NFBC) can be prepared by cultivating a cellulose-producing bacterium in a medium containing a dispersant under agitating and aerobic conditions. Although NFBCs have various applications, their detailed structure and physical properties have not been clarified. Therefore, in this study, we performed detailed structural and physical property analyses of NFBCs to advance their potential applications. Atomic force microscopy and image analysis showed that the average fiber length of NFBCs was approximately 17 µm and fiber widths were 10–15 nm; the aspect ratios of NFBCs were > 1000, which are >10-fold higher than that of 2,2,6,6-tetramethylpioeridine-1-oxyl-oxidized cellulose nanofiber. Shear viscosity measurements showed that the NFBCs exhibited shear-thinning flow behavior even at low concentrations (0.01 wt%). Frequency sweep measurements showed that the storage modulus values were greater than the loss modulus values in the measured frequency range, indicating that the NFBCs were in a stable gel state. Thus, the NFBCs exhibited significantly longer fiber lengths, larger aspect ratios, and excellent viscoelastic properties based on these unique structural features. Our findings will help develop novel applications utilizing the ultrahigh aspect ratio unique to NFBC and its viscoelastic properties.